CONTINUING PROFESSIONAL EDUCATION AND CAREER BUILDING - Rozhnov, Sergey; vViktorovna Poliakova, Iana; Brusnik, Tatyana; Rozhnova, Kseniya; Lvovna, Kunitsyna; Rozchdestvenskaya, Irina; Myltseva, Margarita (Revista Inclusiones, 2020)
Current socio-economic development of Russia is characterized by the large-scale transformation in all areas: consistent transition of the country to the market economy and the formation of new labor market; changing the role of the state in the field of democratization, advancement to civil society, liberalization, openness, etc. This stage is characterized by intensive changes in the field of interaction between the labor market and the educational system. The development of the economy led to the formation of a new qualification structure of professional personnel oriented to the labor market. In accordance with the emergence of new production processes in the industrial sector, in agriculture, consumer goods, services and other spheres, prerequisites were created for changing the qualifications of workers. In turn, employers are reviewing staff requirements in terms of competencies. As the studies show, most employers consider that graduates require additional training in the workplace due to a lack of practical skills. Employers also note a general lack of professional knowledge and inability to independently solve many production issues. The quality of the country’s labor potential is a decisive factor in the economic progress of society. Not only labor productivity, but also the rate of economic growth, and finally, the competitiveness of the Russian economy in the world market, depend on the professional qualifications of graduates at all levels of training from the worker to the civil servant.